Perancangan Komunikasi Visual Jamu Tradisional di Yogyakarta Sebagai Upaya Pelestraian Budaya Lokal : Penelitian - Wahyu Kurnia Dewi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Traditional jamu is a cultural heritage long consumed by Indonesians to maintain health. However, modernization and lifestyle shifts have caused the popularity of jamu to decline, especially among younger generations. This research aims to design effective visual communication to educate the public, particularly youth in Yogyakarta, on the importance of traditional jamu. Utilizing design thinking, semiotics, myth, and visual communication theories, the design process involved research, analysis, and visualization through social media and creative products like tote bags, t-shirts, and notebooks. The result indicates that the designed visual media successfully captured the audience’s interest, educated them culturally, and raised awareness on preserving traditional jamu. The study concludes that visual communication is an effective strategy for preserving local wisdom.